Role and competency model for coordination tasks in municipal health promotion: findings from an integrative review - Patricia Tollmann; Sven Dieterich; Maja Kuchler; Janna Leimann; Laura Lubosch; Vivien Mielenbrink; Pia Rangnow; Stefanie Terhorst; Eike Quilling (BMC Public Health)
Abstract Background Integrated municipal health promotion is becoming increasingly important in promoting health equity. Successful implementation of integrated municipal health promotion processes requires a central coordinator. Therefore, this study investigates which competencies are necessary to successfully manage the extensive coordination tasks. The aim is to present the necessary roles and competencies in a way that can be applied in practice. Methods An integrative review was conducted. As a first step, a systematic search was carried out in the databases LIVIVO, Web of Science and via the EBSCOhost platform (including APA PsycInfo, ERIC, MEDLINE, CINAHL, APA PsycArticles, SocINDEX) using various inclusion and exclusion criteria (e.g. English and German language). The steps of systematic data extraction, data evaluation and data analysis were subsequently carried out. In accordance with the integrative review method, the data were then iteratively compared and synthesised, followed by the final step of presentation and integration in the form of a new model. Results According to the pre-defined inclusion and exclusion criteria, 12 hits were included. The results identified were combined into a concept for a role and competency model. Central competencies for the coordination of municipal health promotion are e.g., public health expertise, interprofessional competencies as well as coordination, communication, and management competencies. Conclusions The role and competency model presents the roles and competencies needed to coordinate integrated municipal health promotion processes and emphasises the need to work intersectorally. The model provides a guide for practical application and can contribute to the selection of qualified staff, professionalisation, training and curriculum development. It can make a quality-assured contribution to the structural development of integrated health promotion at local level. Further research is needed to validate the model in practice. Trial registration This integrative review was not registered beforehand.